Efeito do método de extração e da secagem sobre o conteúdo fenólico e a composição química de quebra-pedra (Phyllanthus amarus e Phyllanthus niruri) - Sousa, Adriana Dutra (2017)
Effect of the extraction method and drying on the phenolic content and chemical composition of stone breaker (Phyllanthus amarus and Phyllanthus niruri) Resumo The genus Phyllanthus, popularly known as quebra-pedra in Brazil, is composed of plants rich in bioactive compounds, mainly phenolics. Drying of raw material and the extraction process are essential to achieve those compounds. Nowadays, "green" extraction techniques are required to reduce the environmental impacts. Among these techniques, ultrasound-assisted extraction (UAE) and pressurized liquid extraction (PLE) stand out. In this study, aqueous extraction from aerial parts of P. amarus and P. niruri was performed using UAE, PLE and conventional extraction. It was evaluated the effect of time, ultrasonic intensity, and liquid/solid (L/S) ratio in UAE and of time and temperature in PLE on total phenolics and gallic acid extraction. The chemical composition of the extracts was determined by UPLC-QTOF-MS/MS in conjunction with chemometric techniques (PCA and OPLS-DA). Also plants drying parameters were investigated. Aerial parts of the two species were dried in a circulating air-drying oven and drying kinetics data were obtained. The effect of air-drying temperature (50, 60 and 70°C) on phenolic content and on chemical composition was also studied. The highest total phenolics content was observed in the extracts obtained by PLE at 192°C/15 min for the two species, but this high temperature led to degradation of some compounds. The extracts obtained by the PLE at 120°C presented a high phenolic content without chemical degradation. The other extraction techniques produced a lower yield of phenolic compounds and higher solvent consumption. Therefore, PLE at a temperature of 120°C and pressure of 110 bar proved to be a suitable method to extract phenolics, including the compounds with medicinal relevance. The chemical composition of the extracts had mainly hydrolysable tannins and flavonoids. With regard to drying, the increase in air-drying temperature reduced the drying time and increased the effective moisture diffusivity. The best evaluated temperature to obtain a higher phenolic content for both species was 60°C. The results indicate the importance of the drying temperature control to maintain the quality of the raw material and the extraction process in obtaining the compounds of interest.